2012
DOI: 10.1002/alr.21079
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the “central sinus”: radiographic findings in patients undergoing revision functional endoscopic sinus surgery

Abstract: Analysis of CT scans of patients undergoing revision FESS for persistent or recurrent CRS frequently reveals persistent anatomical structures or incompletely resected cells associated with persistent mucosal thickening. Meticulous, complete cell group dissection combined with use of angled endoscopy along with identification of possible predisposing structures may aid in the reduction of need for revision surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 32 publications
3
38
0
Order By: Relevance
“…11 Sixty-four percent of patients in this study had residual uncinate; although the residual components varied, this echoed radiologic findings in a previous revision ESS series. 12 …”
Section: Discussionmentioning
confidence: 99%
“…11 Sixty-four percent of patients in this study had residual uncinate; although the residual components varied, this echoed radiologic findings in a previous revision ESS series. 12 …”
Section: Discussionmentioning
confidence: 99%
“…There may be multiple reasons underlying this finding – there is an increasing body of evidence suggesting that diseased sinuses, if left untreated, may lead to failure of the entire surgery. Over the study period, surgeons may therefore have elected to treat patients more comprehensively 20. Others have also pointed to financial incentives for variability in surgical practice 19.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 On the other hand, residual unopened ethmoid cells at the LP is a common finding in patients requiring revision ESS even in most recent studies. 21,22 Detailed knowledge of the radiological and endoscopic sinonasal anatomy is a key to safe and effective ESS. In fact, avoiding complications begins with preoperative preparation.…”
mentioning
confidence: 99%
“…31 This observation was again highlighted in similar studies over the past decade. 22,31,32 In 2013, Gore et al 21 found residual ethmoid air cells on the LP in 79% of 55 patients undergoing revision ESS. These data clearly signify that efficient clearance of ethmoid air cells on the LP remains challenging in certain cases and probably for some surgeons.…”
mentioning
confidence: 99%
See 1 more Smart Citation